Structure and characterization of B2O3 modified yNd(Mg1/2Ti1/2)O3-(1-y)Ca0.8Sr0.2TiO3 ceramics with a near-zero temperature coefficient at microwave frequency. Issue 2 (1st February 2017) - Lin, Shih-Hung; Chen, Yuan-Bin
Abstract: The microstructure and microwave dielectric properties of the yNd(Mg1/2 Ti1/2 )O3 -(1-y)Ca0.8 Sr0.2 TiO3 ceramics system with B2 O3 addition (1 wt%) prepared using the conventional solid-state route were studied. Microwave measurements show an increase in the dielectric constant ( ε r ) and temperature coefficient of the resonant frequency ( τ f ) and a decrease in the quality factor ( Q×f ) with decreasing Nd(Mg1/2 Ti1/2 )O3 content. The 1 wt% B2 O3 addition for 0.7Nd(Mg1/2 Ti1/2 )O3 -0.3Ca0.8 Sr0.2 TiO3 ceramics sintered at 1375 °C show ε r of 39, a Q×f value of 27000 (at 8 GHz), and a near -zero τ f ( −0.4 ppm/°C). As the content of Nd(Mg1/2 Ti1/2 )O3 increases to y=0.9, the highest Q×f value of 35, 000 (GHz) can be observed under 1375 °C sintered temperature.